ANALISA KEBERADAAN BAKTERI Escherichia coli DAN Pseudomonas aeruginosa PADA AIR MINERAL DI KELURAHAN CEMANI KABUPATEN SUKOHARJO - Putri Rahmawati, Nuraini; Siska Wardani, Tatiana; Irma Permatasari, Desy Ayu (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2021)
Clean, potable fresh water is becoming scarce in cities, the river which is the source of it is polluted with various wastes ranging from organic waste, household waste, and industrial waste. Drinks water quality could affects public health, especially mineral water. One of the parameters for the quality requirements of mineral water are the evaluate for Escherechia coli and Pseudomonas aeruginosa bacteria. The aim of this study was to identify the contamination of Escherechia coli and Pseudomonas aeruginosa bacteria in mineral water samples, using the MPN (Most Probable Number) method. The research method uses descriptive research. The research samples of mineral water were taken in stalls around the Duta Bangsa University Surakarta campus is as much 3 (three) samples. Collecting data by laboratory observation, data analysis with descriptive analysis. The results of the study were carried out from seven samples of mineral water, all samples showed there was no Escherechia coli and Pseudomonas aeruginosa bacteria by the MPN method. The conclusion of this study is that there are no Escherechia coli and Pseudomonas aeruginosa bacteria in mineral water sold in stalls around the campus of Universitas Duta Bangsa Surakarta.